Efektivitas Kinerja Kelembagaan Kelompok Tani Hutan Hetven dalam Pengelolaan Hutan Rakyat di Kelurahan Kobekamusa, Kecamatan Kota So’e, Kabupaten TTS - Emiliana Nini Kelen; Maria M. E. Purnama; Astin E. Mau; Lusia Sulo Marimpan (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2026)
Community forests are forests located on land encumbered by property rights. Community forest development is built with the aim of reactivating uncultivated land or idle land to make it more productive so that it can increase the income of community forest farmers while maintaining its ecological functions. One proof of the success of community forest management in NTT occurred in Kobekamusa Village, TTS Regency. The Community Forest Program in Kobekamusa Village is managed by the Hetven Forest Farmers Group, which takes care of 25 ha of local community land that is part of the Kobekamusa Community Forest. The existence of KTH Hetven in managing the Kobekamusa Community Forest has not been able to minimize events outside the group's design. From an institutional perspective, KTH Hetven is still a Beginner Class KTH, it does not yet have complete supporting data, such as the Decree on the Establishment of KTH which was only issued in 2021. To determine the effectiveness of KTH Hetven's institutional performance in this study using SWOT analysis which is limited to the assessment of the identification of internal aspects and external aspects that affect the performance of KTH Hetven. From the results of the study, the internal aspects for strengths consisted of, (1) A clear structure of KTH, (2) Members' responsibility to their positions, (3) The group is run with kinship, (4) The existence of self-help efforts, and (5) Planting types of MPTS. Meanwhile, the weaknesses consist of, (1) The group class is still a beginner group, (2) Limited equipment, (3) Wood processing is still not effective, (4) Failure of MPTS plants, and (5) Delay in administrative completeness. The results of research on external aspects for opportunities consist of, (1) Cooperation of KTH with other stakeholders, (2) Broader timber marketing targets, while the threat factors consist of, (1) The intensity of assistance that is still rare, (2) Limited education and training activities, (3) There is still illegal logging, and (4) Inadequate road access.